2007
DOI: 10.1002/sce.20201
|View full text |Cite
|
Sign up to set email alerts
|

Developing a new teaching approach for the chemical bonding concept aligned with current scientific and pedagogical knowledge

Abstract: ABSTRACT:The traditional pedagogical approach for teaching chemical bonding is often overly simplistic and not aligned with the most up-to-date scientific models. As a result, high-school students around the world lack fundamental understanding of chemical bonding. In order to improve students' understanding of this concept, it was essential to propose a systemic treatment, namely, revising the scientific content, the pedagogical approach, and the assessment methods regarding this concept. Therefore, the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 32 publications
1
60
0
8
Order By: Relevance
“…Coll & Treagust, 2003a, 2003bHilton & Nichols, 2011;Taber, Tsaparlis, & Nakiboğlu, 2012), on the relationship between students' understanding of different aspects of matter (Cakmakci, Leach, & Donnelly, 2006;Crespo & Pozo, 2004;Othman et al, 2008), on understanding materials (Acher, Acár, & Sanmartí, 2007;Krnel et al, 2005;Margel et al, 2008) or on the impact of instruction in order to foster students' understanding of matter (e.g. Adadan, Trundle, & Irving, 2010;Ardac & Akaygun, 2004;Levi Nahum, Mamlok-Naaman, Hofstein, & Krajcik, 2007). In order to address the two research questions (focusing on the four principal aspects and how students progress in understanding matter relating to these aspects), we categorised the studies in two ways: first, for each study we identified which aspects of matter were addressed; second, for each study the span of age or the ranges of grade bands students were drawn from were identified.…”
Section: Characterisation Of Studiesmentioning
confidence: 98%
“…Coll & Treagust, 2003a, 2003bHilton & Nichols, 2011;Taber, Tsaparlis, & Nakiboğlu, 2012), on the relationship between students' understanding of different aspects of matter (Cakmakci, Leach, & Donnelly, 2006;Crespo & Pozo, 2004;Othman et al, 2008), on understanding materials (Acher, Acár, & Sanmartí, 2007;Krnel et al, 2005;Margel et al, 2008) or on the impact of instruction in order to foster students' understanding of matter (e.g. Adadan, Trundle, & Irving, 2010;Ardac & Akaygun, 2004;Levi Nahum, Mamlok-Naaman, Hofstein, & Krajcik, 2007). In order to address the two research questions (focusing on the four principal aspects and how students progress in understanding matter relating to these aspects), we categorised the studies in two ways: first, for each study we identified which aspects of matter were addressed; second, for each study the span of age or the ranges of grade bands students were drawn from were identified.…”
Section: Characterisation Of Studiesmentioning
confidence: 98%
“…A clear distinction can also be made regarding the phase changes that water undergoes so that students will not assume that chemical bonds are broken when water changes from liquid to gas. The lack of fundamental understanding of chemical bonding among high school students around the world can be attributed to the traditional pedagogical approach for teaching chemical bonding that is often overly simplistic and not aligned with the most up-to-date scientific models [7].…”
Section: Methodsmentioning
confidence: 99%
“… El uso confuso y contradictorio del lenguaje relacionado con las interacciones moleculares (Kind, 2004)  La inadecuada simplificación de ciertos modelos y representaciones utilizados al describir la estructura atómico-molecular de la materia (Özmen, 2004;Nahum, 2007;Kronik, 2008;Galagovsky, 2009;Nahum, 2010).  La escasa atención concedida al estudio de las fuerzas intermoleculares en la introducción al enlace químico, así como la excesiva focalización en el concepto de molécula al introducir los conceptos básicos de química, en detrimento de otros tipos de organización microscópica de la materia como las estructuras reticulares y macromoleculares, fundamentales a la hora de interpretar las propiedades de los materiales más comunes (Llorens, 1991;Tarhan, 2008;Schmidt, 2009) Dentro de las interacciones moleculares, el enlace de hidrógeno posee especial importancia por su influencia en las propiedades físicas en ejemplos tan notorios como el papel del agua en la naturaleza y en los procesos biológicos, en la estructura de las proteínas o en las propiedades mecánicas de materiales como el nilón.…”
Section: Son Diversas Las Causas Atribuidas a Estos Hechos Por Difereunclassified